Alternative natural sources for commercialised starches as pharmaceutical excipients; Physicochemical properties and applications - S.U.Kankanamge
Starch is utilised in manufacturing tablets and capsules as a diluent, binder, and disintegrant, dependent on the formulation requirements. Starch is a prominent pharmaceutical excipient due to its non-toxic, non-irritant characteristics, low cost, ease of modification, availability, and versatility in use. Recent findings report that certain commercial starches have the potential to cause allergies, poor compressibility and poor mechanical qualities, together with high importation costs. Different novel starches have been investigated from sources, especially those of tropical origin, such as tubers (sweet potato and cassava) and cereals (rice and sorghum) for physicochemical properties to explore safe and effective excipients. With the improved properties, modified starches such as pregelatinised and acid-treated starches have been developed physically and chemically as multifunctional excipients such as coating agents, super disintegrants, and controlled-release polymers. Comparing the reviewed data with pharmacopeial specifications, the review highlighted pregelatinised starch and acid-modified millet would be beneficial alternatives to commercial starches with their improved stability, solubility, biocompatibility and cost-effectiveness. Hence, the current review attempts to emphasise the physicochemical properties such as pH, bulk and tapped densities, angle of repose of native and modified starches and their uses as binders, disintegrants and diluents in the pharmaceutical industry.